Peningkatan Membaca Notasi Angka terhadap Parguru Malua di Gereja HKBP Sola Gratia Melalui Kegiatan Praktik Lapang Tematik - Silalahi, Jojor Hotma Delima; Batubara, Junita; Sitohang, Desi Damaiyanti; Sihotang, Hot Parulian; Sitanggang, Ronaldo (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
Thematic Field Practice (PLT) is carried out by students of the Music and English Literature Study Program, Faculty of Language and Arts and their supervisors with the aim of realizing an overview of how children's learning conditions outside of school are. Students must be able to apply the knowledge and skills that have been obtained at the Faculty of Language and Arts, HKBP Nommensen University in this Thematic Field Practice (PLT) activity. Thematic Field Practice (PLT) will increase the ability to observe, examine and assess between theory in practice that occurs in the field which in turn can improve the quality of students in observing problems, both in the form of theory application and actual reality. The way of packaging the Thematic Field Practice (PLT) is designed by the supervisor where this will greatly affect the students and make the Thematic Field Practice (PLT) process more effective and interesting. This can be seen when students apply learning to parguru malua at the HKBP Sola Gratia Church, Environment II, Dataran Tinggi Village, East Binjai, Binjai City. This was done because of the collaboration through the MoU with the Mayor of Binjai through the Dataran Tinggi Village, East Binjai. The result is that of the 14 parguru malua who were trained in the form of a choir in singing the song "O Holy Night" in English, only 2 people were not able to sing in a chorus